Determinants in detecting fraud triangle of financial statements on companies registered in Jakarta Islamic Index (JII) period 2012-2018 - Iwan Budiyono; Melati Sari Dewi Arum (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Purpose - The purpose of study was to examine the effect financial statement fraud based on the fraud triangle with a number of variables such as financial stability, external pressure, financial target, personal financial needs, opportunity and rasionalization in companies listed in Jakarta Islamic Index (JII) period 2012-2018.Method - The population are all companies listed in JII period 2012-2018. The sample is 6 companies that were feasible to analyze. The data used in this research is secondary data obtained from the annual report. The data analysis model applied multiple linier regression data panel using SPSS 25.Result - The results showed that the fraud triangle in the categories of financial stability, external pressure, financial targets, personal financial needs, opportunity and rationalization simultaneously affect the fraudulent financial statements. Furthermore financial stability, personal financial needs and opportunity partially negatively related and had no significant effect on financial statement fraud; while external pressures, financial targets and rationalization have positive and significant effects on financial statement fraud on companies listed in JII period 2012-2018.Implication - Companies Registered in JII are suggested to improve the financial performance in accordance with sharia principles.Originality - This research is the first study using multiple linier regression data panel.